A Learning Model for Reflective Micro-Teaching in A Hybrid EFL Classroom: Need Analysis - Fiftinova Fiftinova; Tita Ratna Wulan Dari; Alhenri Wijaya (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2024)
It is essential for graduates of education study program to possess proficient pedagogical skills. This is an important skill for prospective teachers in meeting the demands of the 21st-century learning, where technology has become an instrument that is used on a daily basis in the field of education as well as in the field of industry. Therefore, this study responded to the need for a program that develops a reflective learning model to offer pedagogical improvement for prospective teachers in dealing with technological devices in a hybrid micro-teaching classroom. A qualitative study was conducted through questionnaires and interviews to find out students’ and lecturers’ perspectives on whether a reflective micro-teaching model in a hybrid EFL classroom should be developed. The participants of this study were 57 seventh-semester EFL who had taken the Micro-Teaching subject and 4 lecturers who taught the subject. Data analysis was carried out by calculating the average response scores from the questionnaires and conducting thematic analysis on the interview data. The findings indicated that reflective micro-teaching should be implemented in a hybrid EFL classroom, as perceived by both lecturers and prospective instructors.